Ijtima Wadzifah Haelalah Sebagai Media Dakwah Tarekat Tijaniyah Di Garut - Maulana Karang, Ari (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2018)
Garut Regency has the largest Tarekat Tijaniyah community in West Java, which was spread by Syaikhuna KH Badruzzaman from the Al Falah Biru Islamic Boarding School. One of the methods of da'wah developed is Ijtima Wadzifah Haelalah, which is the reading of the Wadzifah and Haelalah wirid in congregation every Friday afternoon after the Ashar prayer until Maghrib. This activity is carried out in villages in turns and is attended by Tarekat Tijaniyah practitioners and the general public. This study found that Ijtima Wadzifah Haelalah is effective in increasing the number of Tarekat Tijaniyah practitioners and deepening love for the Prophet Muhammad SAW and Sheikh Ahmad Al-Tijani. The recommendation of this study is to make the event more interesting and use media to disseminate information about the activity. Keywords: Tarekat Tijaniyah, Ijtima Wadzifah Haelalah, Tarekat Tijaniyah Dakwah, Tarekat Tijaniyah Garut